2019
DOI: 10.33151/ajp.16.649
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Anxiety among Paramedic Students

Abstract: IntroductionSummative assessments are an established form of assessing student performance, knowledge and ability against learning outcomes. The impact of anxiety on paramedic student success is not well understood but may adversely affect student outcomes. The aim of this study was to explore the origins and incidence of anxiety among paramedic students.MethodDistance and campus-based students from all three years of the Bachelor of Health Science (Paramedicine) program at Whitireia New Zealand were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The small sample size, cross-sectional survey design and potential for self-selection and response bias are limitations of this study. Nevertheless, the sample size achieved is similar to other similar studies [ 47 , 48 ]. The findings may not be representative of the experiences and views of all Australian paramedics; however, there is congruence between our findings and that of other Australians studies drawn from different geographic areas [ 28 ].…”
Section: Discussionsupporting
confidence: 87%
“…The small sample size, cross-sectional survey design and potential for self-selection and response bias are limitations of this study. Nevertheless, the sample size achieved is similar to other similar studies [ 47 , 48 ]. The findings may not be representative of the experiences and views of all Australian paramedics; however, there is congruence between our findings and that of other Australians studies drawn from different geographic areas [ 28 ].…”
Section: Discussionsupporting
confidence: 87%
“…It was indicated that female gender and increasing work years are the most factors associated with paramedics' inactivity and work stress (18). Wills et al (15) conducted a study to assess the prevalence of anxiety among paramedic students in New Zealand and reported that students with previous tertiary education to diploma had a signi cant higher anxiety level (36.72 ± 5.92) than those with prior degree education (31.42 ± 7.58), (P=0.02). The authors concluded that paramedic students' anxiety may be impacted by different course delivery methods and student backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…Another study was carried on the prevalence of Post-Traumatic Stress Disorder (PTSD) and common mental disorder among ambulance personnel and it was reported that the prevalence of anxiety was (15%), general psychological distress was 27%, and PTSD was 11% (14). Another study used the Westside Test Anxiety Scale (WTAS) to measure anxiety and showed that 70% of the participants reported moderate to extremely anxiety, and 87% reported that they became anxious when facing an upcoming summative assessment, and it was concluded that there were high levels of anxiety among the students (15).…”
Section: Discussionmentioning
confidence: 99%
“…We were selected at random to Previous research has reported a high prevalence of anxiety and stress in the paramedic student population with little or no education aimed at managing stress during acutely stressful situations. 1,2 Mindful breathing is a mind-body practice that has been shown to positively influence physiological and psychological measures of stress. 3,4 This study aimed to investigate the effects of mindful breathing on the physiological and psychological stress response of undergraduate paramedic students during simulated clinical skills performance.…”
Section: Contextmentioning
confidence: 99%